Complex oxide interfaces: determination of electronic structure of Oxide–Oxide interfaces by photoemission spectroscopy (adv. mater. 26–27/2010) - Wang, Huiqiong; Altman, Eric I; Broadbridge, Christine; Zhu, Yimei; Henrich, Victor E (Advanced Materials, 2010)
Keywords: dept.phy

Determination of electronic structure of Oxide–Oxide interfaces by photoemission spectroscopy - Wang, Huiqiong; Altman, Eric I; Broadbridge, Christine; Zhu, Yimei; Henrich, Victor E (Advanced Materials, 2010)
A method has been developed to use the finite escape depth of the photoelectrons emitted in ultraviolet photoemission spectroscopy (UPS) to determine the electronic density-of-states at the interface between two dissimilar metal oxides. Ultrathin films of one oxide are grown heteroepitaxially, one monolayer at a time, on a single-crystal substrate of the other oxide, and UPS spectra are taken after each complete monolayer. By comparing experimental UPS spectra with calculated spectra based on specific models of the interfacial structure, the interfacial density-of-states can be extracted. The two oxide systems studied here are NiO-Fe 3O 4 and CoO-Fe 3O 4. The former system is found to have an atomically abrupt interface, with no significant density of interface states. For CoO, however, an interfacial electronic spectrum, different from that of either the substrate or the overlayer, is found. The spatial extent and possible origin of those interfacial states is discussed. © 2010 WILEY-VCH Verlag GmbH &. Co. KGaA, Weinheim.
Keywords: Cobalt; Cobalt compounds; Density of interface state; Dissimilar metals; Electron energy levels; Electronic density; Electronic spectrum; Electronic structure; Emission spectroscopy; Escape depth; Ferumoxytol; Interfacial density; Interfacial state; Interfacial structures; Luminescence of organic solids; Models, Molecular; Monolayers; Nickel; Oxide films; Oxide systems; Oxide-oxide interfaces; Oxides; Photoelectron Spectroscopy; Photoelectron spectroscopy; Photoemission; Photoemission spectroscopy; Single-crystal substrates; Smelting; Spatial extent; UPS spectra; Ultrathin films; Ultraviolet photoemission spectroscopy; X ray photoelectron spectroscopy; article; chemical structure; chemistry; cobalt; cobalt oxide; dept.phy; ferumoxytol; nickel; nickel monoxide; oxide